Renal Sinus Fat Is Expanded in Patients with Obesity and/or Hypertension and Reduced by Bariatric Surgery Associated with Hypertension Remission - Moritz Emilia; Dadson Prince; Saukko Ekaterina; Honka Miikka-Juhani; Koskensalo Kalle; Seppälä Kerttu; Pekkarinen Laura; Moriconi Diego; Helmiö Mika; Salminen Paulina; Nuutila Pirjo; Rebelos Eleni (MDPI, 2022)
Renal sinus fat is a fat depot at the renal hilum. Because of its location around the renal artery, vein, and lymphatic vessels, an expanded renal sinus fat mass may have hemodynamic and renal implications. We studied whether renal sinus fat area (RSF) associates with hypertension and whether following bariatric surgery a decrease in RSF associates with improvement of hypertension. A total of 74 severely obese and 46 lean controls were studied with whole-body magnetic resonance imaging (MRI). A total of 42 obese subjects were re-studied six months after bariatric surgery. RSF was assessed by two independent researchers using sliceOmatic. Glomerular filtration rate (eGFR) was estimated according to the CKD-EPI (Chronic Kidney Disease Epidemiology Collaboration). Patients with obesity accumulated more RSF compared to lean controls (2.3 [1.7-3.1] vs. 1.8 [1.4-2.5] cm(2), p = 0.03). Patients with hypertension (N = 36) had a larger RSF depot compared to normotensive subjects (2.6 [2.0-3.3] vs. 2.0 [1.4-2.5] cm(2), p = 0.0007) also after accounting for body mass index (BMI). In the pooled data, RSF was negatively associated with eGFR (r = -0.20, p = 0.03), whereas there was no association with systolic or diastolic blood pressure. Following bariatric surgery, RSF was reduced (1.6 [1.3-2.3] vs. 2.3 [1.7-3.1] cm(2), p = 0.03) along with other markers of adiposity. A total of 9/27 of patients achieved remission from hypertension. The remission was associated with a larger decrease in RSF, compared to patients who remained hypertensive (-0.68 [ -0.74 to -0.44] vs. -0.28 [ -0.59 to 0] cm(2), p = 0.009). The accumulation of RSF seems to be involved in the pathogenesis of hypertension in obesity. Following bariatric surgery, loss of RSF was associated with remission from hypertension.